2023
DOI: 10.3390/bs13110912
|View full text |Cite
|
Sign up to set email alerts
|

The Mental Health Impacts of a Pandemic: A Multiaxial Conceptual Model for COVID-19

David Dias Neto,
Ana Nunes da Silva

Abstract: The COVID-19 pandemic substantially impacted the mental health of the general population and particularly vulnerable individuals and groups. A wealth of research allows for estimating this impact and identifying relevant factors contributing to or mitigating it. The current paper presents and synthesizes this evidence into a multiaxial model of COVID-19 mental health impacts. Based on existing research, we propose four axes: (1) Exposure to COVID-related events; (2) Personal and social vulnerability, such as p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…For families with school-age children, one of the greatest challenges was managing distance learning, as schools in most countries were closed [1,2]. However, several different factors have been presented to account for why some individuals experienced larger COVID-19 effects compared to others [3]. Personal vulnerability is one such factor, and previous research has shown that families with a child with neurodevelopmental disorders such as Attention Deficit Hyperactivity Disorder (ADHD) and/or Autism Spectrum Disorders (ASDs) found distance learning especially difficult.…”
Section: Introductionmentioning
confidence: 99%
“…For families with school-age children, one of the greatest challenges was managing distance learning, as schools in most countries were closed [1,2]. However, several different factors have been presented to account for why some individuals experienced larger COVID-19 effects compared to others [3]. Personal vulnerability is one such factor, and previous research has shown that families with a child with neurodevelopmental disorders such as Attention Deficit Hyperactivity Disorder (ADHD) and/or Autism Spectrum Disorders (ASDs) found distance learning especially difficult.…”
Section: Introductionmentioning
confidence: 99%
“…Rather than look at how a discipline slowly and organically evolved over a broad swath of time, as in [ 20 ], we instead examined how an acute and unanticipated event that disrupted a wide range of societal institutions might cause a sudden shift in the research topics that a given discipline focuses on. That is, we compared the topics being studied in Clinical Psychology shortly before the start of the COVID pandemic and shortly after the start of the COVID pandemic (cf., [ 21 ]).…”
Section: Introductionmentioning
confidence: 99%